PENGARUH PENERAPAN DEEP LEARNING TERHADAP PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN INFORMATIKA KELAS VIII SMP KRISTEN CITRA BANGSA MANDIRI KUPANG - Toulay, Yulce Getruida; Enstein, Jhon; Fallo, Diana Yanni Ariswati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate the effectiveness of implementing the Deep Learning instructional model in improving student learning outcomes in the topic "Applying Computational Thinking" within the Informatics subject. A quantitative approach with a True-Experimental method was employed in this research. Data were gathered through pre-test and post-test instruments administered to both a control group (N = 14) and an experimental group (N = 18).The results indicated that the implementation of the Deep Learning model had a significant effect on student learning outcomes. The mean pre-test score of the experimental group was 36.00, which increased significantly to 87.22 in the post-test. Meanwhile, the control group using traditional lecture-based learning achieved a mean pre-test score of 26.07 and a post-test score of 40.71. Hypothesis testing using an Independent Samples t-Test yielded t_calculated = -11.066 (df = 30) with a 2-tailed significance value of p < 0.001, indicating the rejection of H0 (p < 0.05). The mean difference of 46.452 points and a large effect size (Cohen's d = 3.943) confirm that the Deep Learning model is highly effective in significantly enhancing student skills and learning outcomes.